The selective properties of verbs in reflexive constructions - Park, K; Karen Elizabeth Park (2012)
This dissertation investigates the relationship between verbs and reflexive markers within reflexive constructions, setting forth the hypothesis that the verb plays a determining role in anaphoric binding. The work builds upon Dalrymple’s (1993) argument that binding constraints are lexically specified by anaphoric elements and demonstrates that reflexive requirements can be lexically specified for distinct groups of verbs, an approach which offers another level of descriptive clarity to theories of anaphoric binding and introduces a means of predicting reflexive selection in domains where syntactic constraints do not readily apply. This is shown to be particularly pertinent in languages with more than one reflexive type that have overlapping syntactic binding domains. The hypothesis is substantiated by data from five typologically distinct languages: English, Dutch, French, Russian, and Fijian. Contributing to this data set, new empirical evidence in favour of previously unrecognized reflexive forms in the Fijian language is introduced in this work. Following Sells et al. (1987), it is demonstrated that reflexive constructions are definable over four different components of linguistic representation and a quadripartite linguistic analysis is, therefore, adopted that incorporates c-structure, f-structure, lexical structure, and semantic structure within a Lexical Functional Grammar theoretical framework. The level of semantic structure is found to be particularly interesting since the realization of a reflexive construction is shown to be influenced by differing semantic requirements between verbs and reflexives. On the basis of several semantic tests, verbs in reflexive constructions are shown to have two different predicate structure types, ‘transitive’ and ‘intransitive’, and reflexive markers are shown to have three different internal semantic structures, ‘strict’ (x,x), ‘close’ (x,f(x)), and ‘near’ (x,y). The syntactic, semantic, and lexical characteristics of the reflexives and verbs analyzed over the data set presented in this work result in the identification of eight different reflexive/verb types and the establishment of two implicational relationships: Reflexive markers in lexically intransitive reflexive constructions have no semantic content. Verbs that take a reflexive argument with a strict (x,x) or close (x,f(x)) internal structure must be intransitive at the semantic component of linguistic structure. These results contribute to our understanding of anaphoric binding theory, directed verb categories, the syntax-semantics interface, and the licensing of multiple reflexive types within a given language.